2016
DOI: 10.1097/meg.0000000000000542
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial overgrowth and diversification of microbiota in gastric cancer

Abstract: ObjectiveMicrobiota is potentially linked to the development of cancer. However, the features of microbiota in gastric cancer remain unclear. The aim of this study was to characterize the gastric microbiota in cancer.MethodsA total of 315 patients, including 212 patients with chronic gastritis and 103 patients with gastric cancer, were enrolled in the study. The bacterial load of gastric mucosa was determined using quantitative PCR. To analyze the biodiversity, structure, and composition of microbiota, amplico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
163
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(187 citation statements)
references
References 46 publications
18
163
0
6
Order By: Relevance
“…This expectation is contradictory to our finding that Hp relative abundance was higher in cases with more advanced disease ( i.e ., higher tumor grade). Consistent with our findings, a recent study of 212 patients with chronic gastritis and 103 GCA cases in China evaluated using quantitative PCR showed that bacterial load in the gastric mucosa was higher in cancer cases than in patients with gastritis, and that the bacterial load correlated positively with the absolute quantity of Hp ( R = 0.38, p < 0.001) . This observation is consistent with a potential role for Hp in tumor progression.…”
Section: Discussionsupporting
confidence: 92%
“…This expectation is contradictory to our finding that Hp relative abundance was higher in cases with more advanced disease ( i.e ., higher tumor grade). Consistent with our findings, a recent study of 212 patients with chronic gastritis and 103 GCA cases in China evaluated using quantitative PCR showed that bacterial load in the gastric mucosa was higher in cancer cases than in patients with gastritis, and that the bacterial load correlated positively with the absolute quantity of Hp ( R = 0.38, p < 0.001) . This observation is consistent with a potential role for Hp in tumor progression.…”
Section: Discussionsupporting
confidence: 92%
“…Although they found no differences in bacterial load and severity of mucosal inflammation, they noted that patients with gastric cancer harboured a significantly increased bacterial load as compared with patients who had chronic gastritis alone, in agreement with our observations. Cancers were also associated with a more diverse microbiota, including Proteobacteria , Firmicutes , Bacteroides , Fusobacteria , and Actinobacteria . These findings and those of other studies confirm frequent bacterial colonisation of the stomach in patients with mucosal atrophy and hypochlorhydria, and support the hypothesis that bacterial overgrowth may contribute to the development of gastric carcinoma …”
Section: Discussionsupporting
confidence: 85%
“…Andersson et al showed that the stomach displayed a diverse microbiota composition when H. pylori is absent or insignificant whereas samples positive for H.pylori were predominated by this bacterium [8]. It was higher in H. pylori -infected patients compared with those uninfected individuals (P=0.005) [9]. The unweighted principal coordinate analysis showed that the communities of microbiota in gastric cancer were more diversified.…”
Section: Dysbiosis Of Gastric Microbiota In H Pylori Associated Gastmentioning
confidence: 99%
“…Five genera of bacteria with potential carcinogic activities were enriched in patients with gastric cancer, including Lactobacillus, Escherichia-Shigella, Nitrospirae, Burkholderia fungorum, and unculturable Lachnospiraceae species. Of particular interest, Nitrospirae was present in all patients with gastric cancer but absent in patients with chronic gastritis [9].…”
Section: Dysbiosis Of Gastric Microbiota In H Pylori Associated Gastmentioning
confidence: 99%